Securing Financial Information in the Digital Realm: Case Studies in Cybersecurity for Accounting Data Protection - Kafi, Md Abdullahel; Akter, Nazma (American Journal of Trade and Policy, 2023)
Securing financial information, especially accounting, is essential in the digital world. This article explores organizations’ challenges in protecting accounting data from evolving cyber threats. By sharing real-life case studies and industry research, we offer suggestions to enhance the security of accounting information. These recommendations include adopting cybersecurity frameworks implementing technical defenses like endpoint protection and network segmentation, following secure coding practices prioritizing user awareness and training, creating incident response and business continuity plans, regularly conducting vulnerability assessments and monitoring, maintaining strong vendor relationships, and ensuring compliance with relevant regulations and standards. By implementing these suggestions, accounting professionals and organizations can strengthen cybersecurity measures. Effectively protect valuable financial data from the ever-growing threat landscape. Taking an approach that combines technical measures, user awareness, incident preparedness, and regulatory compliance is crucial when navigating the digital landscape with confidence and resilience.